'It's more flexible': persistence of women engineers in the academy. (4th May 2017) - Mlambo, Yeukai Angela; Mabokela, Reitumetse Obakeng
ABSTRACT: The under-representation of women in engineering is an issue of concern for policy-makers. While much of the existing literature has focussed on understanding reasons for women's under-representation in engineering and related technical fields, there is a paucity of research that examines why women who are already in engineering persist. This study aims to answer the question, why do women engineers in academe persist in a discipline that is generally perceived to be inhospitable to women. Three main challenges, namely gender discrimination, lack of institutional and disciplinary support, and the rigid nature of the workplace, emerged as key impediments to women engineers in the private sector. In contrast, women engineers in the academy identified the flexibility offered by academic environments, the presence of personal support networks, and a passion for teaching and students as critical factors that influenced their decision to remain in academia.